Colossal sculpture of a Jain Tirthankara - Temples of India Project Team (Jio Institute, 2024)
Seen here is a colossal sculpture of a Jain Tirthankara, standing in kayotsarga (dismissing the body) posture, found in the ruined shrine to the west of the central temple. The inscriptions at the base of the free-standing statues ascribe it to the 16th century CE. The sculpture is carved out of black stone, mostly granite variety.